Advances in the use of the RNA interference technique in Hemiptera. (5th October 2012) - Li, Jie; Wang, Xiao‐Ping; Wang, Man‐Qun; Ma, Wei‐Hua; Hua, Hong‐Xia
Abstract : Abstract RNA interference (RNAi) suppresses the expression of target genes by post‐transcriptional regulation. Because double‐stranded RNA (dsRNA) mediated gene silencing is a conserved mechanism in many eukaryotes, RNAi has become a valuable tool for unveiling gene function in many model insects. Recent research has also shown that RNAi can also be effective in the downregulation of target genes in Hemiptera. In this review, we discuss the use of the RNAi technique in gene functional analysis in hemipterans, highlighting the methods of dsRNA uptake by these insects and discuss the knock‐down efficiency of these techniques. Although the RNAi technique has disadvantages, our primary goal here is to determine whether it can be exploited further in the discovery of new gene functions, and as a pest control strategy, in some important Hemipteran pests.